SUPERFICIAL HEMOSIDEROSIS OF THE CENTRAL NERVOUS SYSTEM - NISHIYAMA, Kohsuke; KATSURAGI, Shoichi; NAKAMURA, Masaaki; MAEDA, Aki (Japanese Journal of National Medical Services, 2001)
Superficial hemosiderosis of the central nervous system (SS) is a rare disease. However, patients with this disease eventually suffer from complete hearing loss, blindness and dementia. Therefore, the quality of life of such patients becomes very low. On the other hand, the early-stage diagnosis of this disease has recently become possible, based on the characteristic MRI findings. In the present the paper, the authors summarized the clinical features of 35 Japanese cases and described the pathological findings observed in one typical case. The predominant symptoms at the onset are a diminution of hearing ability and unsteady gait, especially in the otolaryngological or neurological fields. The possibility of the presence of SS patients among many patients with these two common symptoms exists. Therefore, it is recommended that doctors, especially otolaryngologists and neurologists, should pay close attention to this particular disease.